The stressing effect of shearing in mid-pregnancy of Zandi ewes on live weight and body sizes of twin lambs at the time of birth - Kalhor, M.; Eila, N.; Zarei, A.; Noshary, A. (Diponegoro University, 2023)
This research investigated the effect of stress of mid-pregnancy shorn Zandi ewes on the live birth weight and body sizes of twin lambs. A total of 96 Zandi ewes, confirmed pregnant with twins, were randomly allocated on day 80 of pregnancy into 4 groups, each group containing 6 replicates (each replicate containing 4 sheep). The experimental groups included: 1. Control, 2. Crutched, 3. Sham-Shorn, and 4. Shorn. Blood cortisol concentrations of the ewes in the experimental shorn treat-ment group increased significantly compared to control (P<0.05). The average length of pregnancy in the ewes of the shorn treatment group was 2 and 1.5 days longer than the control and Sham-Shorn groups (P<0.05). Lambs born from ewes given the shorn treatment were heavier at birth as compared to the lambs of the other treatments, as well as having longer body lengths, arms, and legs (P<0.05). In general, the results showed that the ewes that were shorn in mid-pregnancy had a higher cortisol con-centration, and it had a significant effect on the birth weight and sizes of the lambs compared to other treatments.